Pelestarian Benteng Van der Capellen Kabupaten Tanah Datar 2007-2010 - Mawaddah, Bunga Suci; Erniwati, Erniwati (Jurusan Sejarah FIS UNP, 2025)
Fort Van der Capellen, a colonial Dutch heritage site located in Batusangkar City, Tanah Datar Regency, has a long history marked by various functional transformations, including serving as a colonial defense post, Japanese military headquarters, a Teacher Training College (now State University of Padang), and later the Tanah Datar Police Resort office. Since ceasing its official function in 2000, the building fell into neglect and deterioration due to aging and insufficient maintenance. This article examines the preservation efforts carried out by the government through the Batusangkar Cultural Preservation Center between 2007 and 2010, employing the historical method through heuristics, source criticism, interpretation, and historiography. The findings reveal that the preservation process occurred in three stages: first, protection through environmental cleaning in 2007 and phased physical restoration from 2008 to 2010; second, development involving documentation, technical studies, and expert involvement to ensure a planned conservation process; and third, utilization, including the fort’s adaptive reuse as the Office of Tourism, Youth, and Sports of Tanah Datar Regency and its designation as a National Cultural Heritage site.